MODERNIZATION OF DAYAH EDUCATIONAL INSTITUTIONS (CASE STUDY IN DAYAH MODERN EDUCATION FOUNDATION ARUN LHOKSEUMAWE) - Syarifah Rahmah; Husaini Husaini; Samsul Bahri (JURNAL TARBIYAH, 2021)
This study examines the movement of modernization of education dayah in recent decades. The object of this research is centered on Dayah Modern Education Foundation Arun Lhokseumawe, which is a dayah that has successfully developed the education system by using the approach of modern spirituality reality while maintaining the quality of education. This research uses qualitative approach through case study model design. Based on the findings of researchers concluded that modernization is carried out the system of vision-mission elaboration, implementation and elaboration of dayah curriculum that combines the national curriculum (school) with the local curriculum (dayah) that supports the perfection of the teaching and learning system, learning tools or media used, teaching and learning methods used, as well as a modern evaluation or assessment system to know the success rate of student learning, or santriwan and santriwati. The process of modernization of education in modern dayah Arun Education Foundation began with the establishment of MTs and MA dayah modern YAPENA in 2009 as an application of the vision of realizing a quality modern dayah to give birth to a generation of Muslims who believe and fear.